R&D and human capital policies as determinant factors for a company's performance and profitability - Elena Valentina Țilică (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: This paper investigates the impact of R&D expenses and human capital related indicators on the performance and profitability of companies from the European pharmaceutical sector. Design/methodology/approach: The database includes 26 listed companies from different European countries in the period 2011-2017. The study consists in a panel data analysis, using either fixed or random effects based on the results of the Hausman test. Findings: The results show that R&D expenses and CEO-chairman duality have a positive impact both on a company's performance and profitability and their effects can be seen starting with the year they were employed. However, a CEO change has a more pronounced impact on performance indicators which is observed starting with the year following the one it was performed. Furthermore, while pension related expenses prove to have no effect on either profitability rates or performance margins, an increase of employee productivity shows a positive impact only on the company's performance. Research limitations/implications: These results show that all parties interested in the development of a company and the increase of its profitability will have a tough mission when trying to find the correct policies to implement, as some that improve a firm's performance might not influence its profitability. Nonetheless, R&D related expenses could provide a solid policy for the European pharmaceutical sector as they appear to have a positive impact on both profitability and performance. However, the relative low number of companies included in the database limits the degree of generalization of the obtained results, especially considering a global perspective. Furthermore, the short analysis period could generate biased results when considering the impact of the human capital indicators on a company's results as their impact could be seen in a more prolonged time. In order to test the robustness of the findings, additional years should be included in the database, taking into consideration also non-stable periods. Originality/value: The paper includes a wide array of indicators (related to R&D, corporate governance and human capital, alongside the typical financial indicators) to provide a comprehensive picture of the possible determinants of a company's profitability and performance.
Keywords: G30; 330; profitability rates; company performance; human capital; R&D expenses; CEOchairman duality